Taxonomic revision of the Psylliodes picipes species group (Coleoptera: Chrysomelidae: Galerucinae) with description of a new species from Central Apennines - D’alessandro, Paola; Salvi, Daniele; Berrilli, Emanuele; Biondi, Maurizio (Zootaxa, 2026)
The Central Apennines host a taxonomically complex scenario within the genus Psylliodes. Building on previous molecular evidence, we conducted a detailed morphological and morphometric investigation of Psylliodes biondii, P. picipes, and P. springeri to clarify the taxonomic status of the Maiella population previously attributed to P. biondii. Our results support the description of Psylliodes caroli sp. nov., excluding the hypothesis that the Maiella population represents a disjunct population of P. picipes. We provide a comprehensive assessment of the distinctiveness of each species within the Psylliodes picipes species group, and present a diagnostic key based on external morphological characters, as well as the median lobe of the aedeagus, and spermatheca.